Redescription of mature larva and biological notes on the nominotypical subgenus Gonioctena Chevrolat (Coleoptera: Chrysomelidae: Chrysomelinae) from South Korea - Cho, Hee-Wook (Zootaxa, 2019)
The mature larvae of the nominotypical subgenus Gonioctena Chevrolat, 1836 are redescribed and illustrated: G. coreana (Bechyně, 1948), G. gracilicornis (Kraatz, 1879), G. jacobsoni (Ogloblin & Medvedev, 1956), and G. viminalis (Linnaeus, 1758). The tubercular pattern, chaetotaxy, and shape of tarsugulus were used as diagnostic characters for the species determination of Gonioctena s. str. larvae. The literature on larval morphology of each species has been summarized. Furthermore, the biology, behavior, and host plant are presented. Ovoviviparity is newly reported in G. coreana.